Snake Venom Metalloproteinases from Puff Adder and Saw-Scaled Viper Venoms Cause Cytotoxic Effects in Human Keratinocytes - Keirah E. Bartlett; Adam Westhorpe; Mark C. Wilkinson; Nicholas R. Casewell (Toxins)
Snakebite envenoming is a neglected tropical disease that causes substantial mortality and morbidity globally. The puff adder (Bitis arietans) and saw-scaled viper (Echis romani) have cytotoxic venoms that cause permanent injury via dermonecrosis around the bite site. Identifying the cytotoxic toxins within these venoms will allow for the development of targeted treatments to prevent snakebite morbidity. In this study, venoms from both species were fractionated using gel filtration chromatography, and a combination of cytotoxicity approaches, SDS-PAGE gel electrophoresis, and enzymatic assays were applied to identify the venom cytotoxins in the resulting fractions. Our results indicate that snake venom metalloproteinase (SVMP) toxins are responsible for causing cytotoxic effects across both venoms. The PI subclass of SVMPs is likely the main driver of cytotoxicity following envenoming by B. arietans, while the structurally distinct PIII subclass of SVMPs is mostly responsible for conveying this effect in E. romani venom. Identifying distinct SVMPs as cytotoxicity-causing toxins in these two African viper venoms will facilitate the future design and development of novel therapeutics targeting these medically important venoms, which in turn could help to mitigate the severe life- and limb-threatening consequences of tropical snakebites.